Tingkat Premenstrual Syndrome (PMS) Dengan Kejadian Excessive Daytime Sleepiness (EDS) Pada Mahasiswi - Rinditya Rafa Nadidah; Farida Hayati; Nian Afrian Nuari (STIKES dan AKZI Karya Husada Kediri, 2022)
Premenstrual Syndrome (PMS) is a collection of symptoms or complaints in the form of physical, emotional, and behavioral that occur 7-10 days before menstruation. Many theories state the cause of PMS, but one of the factors suspected of causing PMS is hormonal. The imbalance of estrogen and progesterone hormones allows a person to experience Excessive Daytime Sleepiness (EDS). This study aims to analyze the correlation between the level of Premenstrual Syndrome (PMS) with the incidence of Excessive daytime sleepiness (EDS) in undergraduate nursing students at STIKES KaryaHusada Kediri. The research design used in this study is correlated with a cross-sectional approach. The sample in this study was 165 people who were the whole population (Total Sampling). Data analysis using Spearman rank. The results showed that almost half of the respondents had moderate PMS and most of the respondents had EDS. Analysis with the Spearman rank statistical test obtained an -value of 0.001 with an error level of =0.05, which means that there is a relationship between the level of Premenstrual Syndrome (PMS) and the incidence of Excessive Daytime Sleepiness (EDS) with the strength of the weak category (r=0.252). Many factors can affect PMS and EDS conditions, perhaps one of the factors that can play a role in the form of bad living habits such as lack of physical activity and bad habits the form of playing with gadgets before going to bed. Thus, changing life habits for the better such as increasing physical activity and reducing bad habits of playing with gadgets before bed with maximum use of 30 minutes can be a solution to prevent the occurrence of EDS, besides that sufficient physical activity can also reduce the perceived risk of PMS severity. and also avoiding stressful and fatigue conditions can be the solution.